Misclassification of coffee consumption data and the development of a standardised coffee unit measure. Issue 1 (2nd May 2019) - Poole, Robin; Ewings, Sean; Parkes, Julie; Fallowfield, Jonathan A; Roderick, Paul
Abstract : Background: Associations of coffee consumption with multiple health outcomes have been researched extensively. Coffee consumption, usually reported in cups a day, is a heterogeneous measure due to numerous preparation methods and cup sizes, leading to misclassification. This paper develops a new 'unit' measure of coffee and uses coffee consumption data from a representative sample of the UK population to assess misclassification when cup volume and preparation type are not taken into account. Methods: A coffee unit measure was created using published estimates of caffeine and chlorogenic acid concentrations, and applied across volumes and preparation types. Four-day food diary data in adults from the UK National Diet and Nutrition Survey (NDNS; 2012–2016) were used to quantify coffee intake. Participant self-reported cups a day were compared with cups a day standardised by (a) 227 mL volume and (b) 227 mL instant coffee equivalents (unit measure), and the degree of misclassification was derived. Sensitivity analyses were conducted to model coffee drinking preferences of different populations and caffeine:chlorogenic acid weighting assumptions of the unit measure. Results: The NDNS sample consisted of 2832 adult participants. Coffee was consumed by 62% of participants. Types varied, with 75% of caffeinated coffee cups being instant, 17% filter, 3% latte, 2% cappuccino, 2% espresso and <1% other types. Comparing reported cups to volume-standardised cups, 84% of participants had correct classification, and 73% when using the coffee unit measure, 22% underestimated and 5% overestimated, largely by one cup. Misclassification varied by gender, age and income. Sensitivity analysis highlighted the benefits of using the unit measure over volume alone to cater for different populations, and stability of the unit composition assumption. Conclusion: Cup volume and preparation type should be taken into account, through the application of a standardised coffee unit measure, when coffee consumption is classified in future research studies.